Resonance Raman Spectroscopy of Conducting Polypyrrole Nanotubes: Disordered Surface versus Ordered Body - Trchová, Miroslava; Stejskal, Jaroslav (The journal of physical chemistry. A, 2018)
Polypyrrole nanotubes rank among the most conducting forms of organic semiconductors. They are prepared by the oxidation of pyrrole in the presence of methyl orange. Other organic dyes, viz. ethyl orange, Acid Blue 25, and Acid Blue 129, have been used in the present study to prepare globules or nanofibers. The resulting polypyrroles were studied in detail by Raman spectroscopy. The apparent paradox when a dye contribution to spectra is absent with 785 nm excitation line and present with shorter wavelengths is explained by the resonance character of the Raman scattering, which allows the separation of the contributions from the polypyrrole surface and from the bulk. These differ depending on the laser excitation wavelength and the position of absorption maximum of the individual dyes in ultraviolet-visible spectra and affect both the laser-penetration depth and observation of the resonance effect. The spectra are discussed in terms of different ordering of polymer chains in individual morphologies. The correlation between conductivity, surface areas, and the proportions of ordered and disordered polypyrrole phases at the surface and in the interior of nanostructures is proposed and established using resonance Raman spectroscopy.